Non-healing chronic cutaneous abscess wound infected with Proteus mirabilis in a Shami goat - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Nadarajah, Abraham Gabriel; Saharee, Abdul Aziz; Saad, Mohd Zamri; Roslim, Noorashimah (Pashupati Foundation India, 2013)
A wound is the disruption in the continuity of skin. Infected wound leads to collection of pus in a cavity formed by disintegration of tissues within the dermis or deeper skin tissues leading to cutaneous abscess. Cutaneuos abscesses wounds are common in goats and sheep but infection due to Proteus mirabilis (P. mirabilis) is very rare. In this case report, a Shami goat which had a ruptured abscess at the neck and head region was initially suspected for caseous lymphadenitis (CLA) caused by Corynebacterium pseudotuberculosis (C. pseudotuberculosis) however, the isolation and identification of pus and blood swab samples in an aseptic manner revealed the presence of Proteus species. The Proteus species showed resistance to wide range of antibiotic used in the treatment and causes a non healing abscess wound in the Shami goat.